(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
African Union (AU) Law offers some protections for environmentally displaced people, though a specific ’environmental refugee’ category is not explicitly defined. The AU’s 1969 Convention Governing the Specific Aspects of Refugee Problems in Africa, while not explicitly mentioning environmental factors, includes those displaced by ’events seriously disturbing public order’. This broad definition could be interpreted to include individuals displaced by climate change or natural disasters. The Kampala Convention, the AU’s agreement on internally displaced persons, explicitly covers those fleeing natural or human-made disasters. This document explores the legal protections for environmentally displaced individuals under African Union Law, focusing on the 1969 Convention Governing the Specific Aspects of Refugee Problems in Africa and the Kampala Convention. It examines how these frameworks address displacement caused by climate change and natural disasters, despite the absence of a specific environmental refugee category.